2018
DOI: 10.1186/s41938-017-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fusarium solani in transgenic insect-resistant cotton plants treated with silver nanoparticles from Prosopis glandulosa and Pluchea sericea

Abstract: The phytosynthesis of nanoparticles is a green chemistry approach that combines nanotechnology and bioactive compounds of plants. The aim of this study was to evaluate the effect of silver nanoparticles (AgNPs) from Prosopis glandulosa and Pluchea sericea, respectively, on the control of Fusarium solani previously inoculated in the rhizosphere of transgenic insect-resistant cotton plants. The results showed that the weekly application of AgNPs from P. glandulosa and P. sericea caused a diminution of fungal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Nanoscience leads to the development of low-cost, environmentally friendly nanomaterials, which initiates the disease resistance power of crops exposed to nano-products ( Patra and Baek. 2014 ; Abdelmoteleb et al, 2018 ). Previous literature studies have reported the various fungal species, Fusarium , Verticillium , Alternaria , Penicillium, and Trichoderma , employed for nanoparticle synthesis ( Hassan et al, 2019 ; Mohamed et al, 2020 ; Badawy et al, 2021 ; Shaheen et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Nanoscience leads to the development of low-cost, environmentally friendly nanomaterials, which initiates the disease resistance power of crops exposed to nano-products ( Patra and Baek. 2014 ; Abdelmoteleb et al, 2018 ). Previous literature studies have reported the various fungal species, Fusarium , Verticillium , Alternaria , Penicillium, and Trichoderma , employed for nanoparticle synthesis ( Hassan et al, 2019 ; Mohamed et al, 2020 ; Badawy et al, 2021 ; Shaheen et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The polar extracts (ethanolic and aqueous) of the leaves have displayed antifungal activity and the alkaloid rich fraction derived of the extracts recorded higher activity [21,22,50]. Besides, the aqueous extract has been used to generate silver nanoparticles with antibacterial and antifungal activity [51,52].…”
Section: Prosopis Glandulosamentioning
confidence: 99%
“…extracts or chemical constituents to the control of phytopathogenic fungi could be potentiated through the formulation of nanoparticles. Silver nanoparticles (AgNPs) obtained from aqueous leaf extract of P. glandulosa inhibited the in vitro and in vivo growth of F. solani in cotton plants [52], and zinc oxide nanoparticles (ZnONPs) synthesized with aqueous extract from P. farcta pods exhibited antifungal activity against 10 clinical isolates of C. albicans [87].…”
Section: Antifungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants generally have biosurfactant molecules such as alkaloids, saponins, tannins, glycosides, flavonoids, and phenols. Thus, the materials prepared by the green synthesis method are a potential candidate for larvicidal activity and reducing the accumulation of toxic residues in the aquatic organisms. , …”
Section: Introductionmentioning
confidence: 99%